The impact and predictive value of refeeding syndrome on the short-term prognosis of patients with severe stroke: a retrospective cohort study - Zhang, Wei; Zhang, Shengxiang; Tang, Yun; Yu, Tao (Frontiers in Nutrition, 2026)
IntroductionRefeeding syndrome (RFS) may have adverse effects on patients. However, the impact of RFS on the prognosis of severe stroke patients remain unclear. This study aims to explore the impact on short-term prognosis of patients with severe stroke.MethodsA total of 305 patients were included for retrospective analysis. The electrolyte changes and short-term prognosis between RFS and Non-RFS (NRFS) groups of patients were compared. Besides, the risk factors for prognosis of patients and the predictive efficacy of RFS in patient prognosis were analyzed.ResultsThe new acute liver injury (ALI), new acute kidney injury (AKI), new mechanical ventilation (MV), mortality within 28 d, and mRS scores at the discharge were higher in the RFS group than in the NRFS group (p < 0.05). The serum phosphorus level in the RFS group decreased after EN compared to before EN (p < 0.05). The area under the ROC curve (AUC) of RFS for predicting poor prognosis in patients with severe stroke was 0.678, with a sensitivity of 64.7%, and a specificity of 61.4%.ConclusionRFS is an independent risk factor for the patient’s functional prognosis, therefore, medical staff should screen high-risk populations as early as possible and provide preventive treatment according to the guidelines.